Extending the spectral operation of multimode and polarization-independent power splitters through subwavelength nanotechnology - Fernández de Cabo, Raquel; González–Andrade, David; Cheben, Pavel; Velasco, Aitor V. (Optics and laser technology, 2025)
•This paper introduces a pioneering 3-dB power splitter based on a symmetric Y-junction, enhanced by two distinct subwavelength grating metamaterial geometries for the silicon-on-insulator platform.•The device exhibits high performance for multimode and dual-polarization operation with relaxed fabrication tolerances.•The proposed design, to the best of our knowledge, achieves the broadest simulated bandwidth reported for a multimode and dual-polarization power splitter. It spans over 700 nm (1300 – 2000 nm) for the fundamental and first-order transverse-electric modes, maintaining excess losses below 0.2 dB, and extends over 500 nm (1300 – 1800 nm) for the fundamental transverse-magnetic mode, with losses under 0.3 dB.•Experimental measurements demonstrate losses below 0.2 dB for transverse-electric modes across the 1430 – 1680 nm wavelength range, and under 0.4 dB for the fundamental transverse-magnetic mode within the 1430 – 1630 nm spectrum, even when subject to fabrication deviations of ± 10 nm. Power splitters play a crucial role in virtually all photonic circuits, enabling precise control of on-chip signal distribution. However, state-of-the-art solutions typically present trade-offs in terms of loss, bandwidth, and fabrication robustness, especially when targeting multimode operation. Here, we present a novel multimode 3-dB power splitter based on a symmetric Y-junction assisted by two regions of subwavelength grating metamaterials with different geometries. The proposed device demonstrates high-performance for multimode and dual-polarization operation with relaxed fabrication tolerances by leveraging the additional degrees of freedom offered by two distinct geometries of subwavelength metamaterials to control mode evolution. Our design achieves, to the best of our knowledge, the widest operational bandwidth reported to date for a nanophotonic multimode silicon power splitter. Simulations for a standard 220-nm-thick silicon-on-insulator platform predict minimal excess loss (< 0.2 dB) for the fundamental and the first-order transverse-electric modes over an ultra-broad 700 nm bandwidth (1300 – 2000 nm). For the fundamental transverse–magnetic mode, losses are less than 0.3 dB in the 1300 – 1800 nm range. Experimental measurements validate these predictions in the 1430 – 1630 nm wavelength range, demonstrating losses < 0.4 dB for all three modes, even in the presence of fabrication deviations of up to ± 10 nm. We believe that this device is suitable for the implementation of advanced photonic applications requiring high–-performance distribution of optical signals, such as programmable photonics, multi-target spectroscopy and quantum key distribution.